2011
DOI: 10.1021/cm102889q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strontium Substitution on the Structure of 45S5 Bioglasses

Abstract: Strontium substitution has been found to have a beneficial effect on tissue growth in traditional bioglasses. In this paper, we have studied the effect of SrO/CaO substitution on the structure of 45S5 bioglasses in the series of 46.1SiO 2 3 24.4Na 2 O 3 (26.9Àx)CaO 3 2.6P 2 O 5 3 xSrO (x = 0, 1, 5, 10, 15) compositions using molecular dynamics (MD) simulations with effective partial charge potentials and a combination of constant temperature and pressure (NPT) and microcanomical (NVE) ensembles. The calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
136
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(168 citation statements)
references
References 53 publications
26
136
2
4
Order By: Relevance
“…The Sr-O coordination number was between four and five in the borosilicate glass, in contradiction to our results, but it was between seven and eight for the tin silicate glass and around seven in other computational studies [13,14].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The Sr-O coordination number was between four and five in the borosilicate glass, in contradiction to our results, but it was between seven and eight for the tin silicate glass and around seven in other computational studies [13,14].…”
Section: Resultscontrasting
confidence: 99%
“…Molecular dynamics (MD) simulations provide the atomic structure of the glass, as well as enabling computation of large-scale materials properties. We and others have previously used MD simulations to elucidate the connection between atomic structure and dissolution behaviour of a variety of silicate [20][21][22][23][24][25][26][27] and phosphate glasses [28][29][30] intended for implantation, including strontium-containing silicate glass [13,14]. However, there have been no simulations of Sr in phosphate glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide distribution of the Si-O-Si angle from ~120° to 180° is consistent with the reported results. 38,39) According to previous studies, 43,48) the introduction of a modifier will cause the decrease of the Si-O-Si angle in the silicate network. The average angle of the Si-O-Si, listed in Table 5, slightly decreases from ~155° to 151° with increasing the V 2 O 3 content, this may be an indication that V 2 O 3 act as a modifier in this tetrahedral network.…”
Section: Local Structure Of the Meltsmentioning
confidence: 96%
“…25 Many studies have been systematically conducted and revealed shortrange and medium-range structural features utilizing MD simulation in various glass systems such as sodium silicate glasses, 26 aluminosilicate glasses, 27 lithium disilicate glasses, 28 cerium aliminophosphate glasses, 29 europium-doped silicate glasses, 30,31 erbium-doped sodium silicate glasses, 32 lithium vanadophosphate glasses, 33 and bioactive glasses. [34][35][36] However, MD simulation of nuclear waste glasses has been limited due to the lack of pairwise potential sets for boron. With the recent development of modified composition-dependent pairwise potential sets, it is now possible to simulate complex glass compositions.…”
Section: Introductionmentioning
confidence: 99%